UJI KUAT TEKAN DAN KEAUSAN BAHAN KAMPAS REM DARI KOMPOSISI TEMPURUNG KEMIRI DAN SERAT BAMBU - Thahir, Ahmad (JFT: Jurnal Fisika dan Terapannya, 2018)
It has been tested the performance comparison between gasoline water pump and LPG water pump machine in order to determine the engine temperature and the water discharge generated by gasoline pump ar engine and LPG fuel pump machine and fuel consumption of used machine the. The results showed that the temperature of the gasoline-fueled water pump and the elpyi-fueled water pump machine were 86oC and 75,33oC for the environmental temperature of 32oC, while at the temperature of 40oC the temperature of the gasoline water pump and the water pump fired elpyi successively is 87,33oC and 79,33oC. Water discharge generated by gasoline engine and gas pump water pump machine in a row is 0,28 m3/s and 0,215 m3/s for environmental temperature 32„aC, whereas at temperature environment 40oC large water discharge produced by gasoline water pump and LPG water pump machine are 0,29 m3/s is and 0,215 m3/s. Is fuel consumption of gasoline water pump machine 150 gram suck water 2,55 m3, while the fuel consumption of LPG-fueled pumping engines amounted to 124 grams of water sucking as much as 2,55 m3. Key Words: Water pump, Engine temperature, Water discharge, Gasoline, LPG.